Does it matter? essays on man's relation to materiality - Watts, Alan. (Novato New World Library, 2007)
This classic series of essays represents Alan Watts's thinking on the astonishing problems caused by our dysfunctional relationship with the material environment. Here, with characteristic wit, a philosopher best known for his writings and teachings about mysticism and Eastern philosophy gets down to the nitty-gritty problems of economics, technology, clothing, cooking, and housing. Watts argues that we confuse symbol with reality, our ways of describing and measuring the world with the world itself, and thus put ourselves into the absurd situation of preferring money to wealth and eating the menu instead of the dinner.
Originally published: New York : Pantheon Books, 1970.
Keywords: Conduct of life